Activated ezrin controls MISP levels to ensure correct NuMA polarization and spindle orientation - Kschonsak, Yvonne Theresa; Hoffmann, Ingrid (Journal of cell science, 2018)
Skip to Next Section - Correct spindle orientation is achieved through signaling pathways that provide a molecular link between the cell cortex and spindle microtubules in an F-actin-dependent manner. A conserved cortical protein complex, composed of LGN (also known as GPSM2), NuMA (also known as NUMA1) and dynein-dynactin, plays a key role in establishing proper spindle orientation. It has also been shown that the actin-binding protein MISP and the ERM family, which are activated by lymphocyte-oriented kinase (LOK, also known as STK10) and Ste20-like kinase (SLK) (hereafter, SLK/LOK) in mitosis, regulate spindle orientation. Here, we report that MISP functions downstream of the ERM family member ezrin and upstream of NuMA to allow optimal spindle positioning. We show that MISP directly interacts with ezrin and that SLK/LOK-activated ezrin ensures appropriate cortical MISP levels in mitosis by competing with MISP for actin-binding sites at the cell cortex. Furthermore, we found that regulation of the correct cortical MISP levels, by preventing its excessive accumulation, is essential for crescent-like polarized NuMA localization at the cortex and, as a consequence, leads to highly dynamic astral microtubules. Our results uncover how appropriate MISP levels at the cortex are required for proper NuMA polarization and, therefore, an optimal placement of the mitotic spindle within the cell. - This article has an associated First Person interview with the first author of the paper.
Gesehen am 18.11.2019